Optimalisasi Pengelolaan Toko Bunga: Pengembangan Aplikasi Kasir Berbasis Desktop - Dinanti, Anastasya Aprilla Eka; Pangestu, Dimas Puji; Basatha, Rizky (Al-DYAS, 2025)
This research presents the development of a sales data management system application for desktop-based flower shops. In the context of an ever-evolving business, florists face challenges in managing transactions and inventory manually, which often results in inefficiencies and errors. Therefore, this research aims to design and implement an application that can simplify the management process. The application is designed with an intuitive user interface and uses Microsoft SQL Server as the database. Through functional and performance testing, the application demonstrated its ability to record transactions, manage stock, and generate sales reports in real-time. The results of this study are expected to improve the operational efficiency of flower shops and provide a solid basis for better decision-making.